Teacher’s Strategies in Teaching English to Deaf Students in A Special School Sorong - Heriyanti; Tapada, Jeane Susan; Uluelang, Kris; Umasugi, Putri Jalila; Wahab , Isnaeni (Universitas Islam Ahmad Dahlan (UIAD), 2023)
The researcher investigated the teacher's strategies for teaching English at SMPLB Kota Sorong. This research aimed to discover teaching strategies English teachers apply in teaching English to deaf students. The researcher used descriptive qualitative research. The subject of this research was an English teacher teaching English to 8 deaf students. A total sampling was used to select the participants by conducting observation and interviews to gather data. Data analysis techniques were data reduction, data analysis, and conclusion. The researcher discovered two main strategies as the teaching strategies used in teaching English to deaf students, repetition, and visualization strategy. They were acquired to optimize the learning process in the deaf students’ classroom. In addition, if the deaf students were not yet capable of learning independently, the teacher would tolerate their conditions and abilities. This strategy benefited the teacher in guiding and controlling the material learned to improve the students' understanding. Because deaf students learn through their eyes first, using visual media or natural objects can assist them in learning English effectively.